Language in corticobasal syndrome: a systematic review - Almeida,Isabel Junqueira de (2021)
ABSTRACT. Language is commonly impacted in corticobasal syndrome (CBS). However, the profile and type of language assessment in CBS are poorly studied. Objective: To identify language impairments in CBS. Methods: A search was performed in the Medline/PubMed database, according to the PRISMA criteria, using the keywords “corticobasal syndrome” OR “corticobasal degeneration” AND “language”. Articles on CBS covering language assessment that were written in English were included, with no constraints on the publication date. Results: A total of 259 articles were found and 35 were analyzed, consisting of 531 participants. Twenty-eight studies showed heterogeneous language deficits and seven mentioned nonfluent primary progressive aphasia. The most used tests were the Western Aphasia Battery (8 studies) and the Boston Naming Test (8 studies). Conclusion: It was not possible to identify a unique linguistic profile in CBS.